CLINICAL AND PSYCHOLOGICAL ASSESSMENT OF THE LIMITED RESPONSIBILITY TO “UNDERSTAND, EVALUATE AND MAKE DECISIONS” IN THE CIVIL PROCESS - Zaviazkina, Natalia (PSYCHOLOGICAL JOURNAL, 2018)
Growing demands for substantiating expert opinions, and dynamic changes in legislation, dictate the need for create an integrated system that would facilitate the unification of modern and traditional principles of diagnosing mental disorders with the principles of forensic expert activity using modern methods of psychological diagnosis. One of the most important tasks during the examinations in the civil process is the development of diagnostic criteria for limited legal capacity, the establishment of its "lower" and "upper" boundaries. This is especially important in view of the fact that the partial possibility of a limitedly capable citizen to be responsible (to understand the meaning of one’s own actions and the need to fulfill obligations, the ability to retain them in memory, the ability to perform actions under external regulations on the part of the trustee) is one of the significant grounds for differentiation of the limited incapacity and incapacity. In the course of the research it was proved that the growing demands for substantiating expert opinions, and dynamic changes in legislation, dictate the need for create a integrated system that would facilitate the unification of modern and traditional principles of diagnosing mental disorders with the principles of forensic expert activity using modern methods of psychological diagnosis. Important questions in the methodological approaches in forensic expertology in the civil process are, firstly, the issue of the legislative framework: the subject, the object, the grounds and the order of appointment and the general principles of conducting expert research. Secondly, the consideration of general principles of forensic expert activity of psychologists: stages and methods of expert research with observance of all requirements, psychological diagnosis of mental disorders and the establishment of pathopsychological register-syndromes, establishing the correlation between medical and legal criteria. Analyzed data suggest that to assess the ability of the subject to understand the significance of their actions and the ability to predict and manage such actions, it is necessary to identify several criteria: the degree of manifestation of changes in cognitive functions, the degree of expression of changes in the emotional-volitional and motivational sphere, the violation of prognostic and critical functions.